2016
DOI: 10.1002/ajh.24374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of racial variations in disease characteristics, treatment patterns, and outcomes of patients with chronic lymphocytic leukemia

Abstract: The impact of race on outcomes of patients with chronic lymphocytic leukemia (CLL), the most common leukemia in the west, is not well studied. We aimed to understand racial variations in clinical and disease characteristics, treatment patterns, and outcomes in patients with CLL. We utilized the Mayo Clinic CLL database to perform an analysis of these characteristics and natural history of non-white (NW) compared to white (W) CLL patients. Differences by race in median overall survival (OS) and time-to-first-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Chronic lymphocytic leukemia (CLL) is the most common type of leukemia in the Western world and half of the patients with this condition require treatment within 5 years of diagnosis. 1 According to Danish national CLL guidelines, 2,3 standard first-line treatment includes fludarabine, cyclophosphamide plus rituximab (FCR) for younger, fit patients, 4,5 and bendamustine plus rituximab (BR) for patients above 65 years old. 6,7 Furthermore, chlorambucil, either as monotherapy or com-bined with anti-CD20 antibodies (CD20-chlorambucil), is recommended for unfit patients with significant comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic lymphocytic leukemia (CLL) is the most common type of leukemia in the Western world and half of the patients with this condition require treatment within 5 years of diagnosis. 1 According to Danish national CLL guidelines, 2,3 standard first-line treatment includes fludarabine, cyclophosphamide plus rituximab (FCR) for younger, fit patients, 4,5 and bendamustine plus rituximab (BR) for patients above 65 years old. 6,7 Furthermore, chlorambucil, either as monotherapy or com-bined with anti-CD20 antibodies (CD20-chlorambucil), is recommended for unfit patients with significant comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…This study was approved by the Mayo Clinic Institutional Review Board. Patients diagnosed with CLL between January 1, 2000 and December 26, 2019 were identified from the Mayo Clinic CLL Database, which includes consecutive CLL patients who were evaluated within one year of diagnosis in the Division of Hematology at Mayo Clinic, Rochester, MN [7]. All patients provided an informed consent form.…”
Section: Dear Editormentioning
confidence: 99%
“…Prior studies suggested that practice setting is associated with survival disparities in lymphomas . Furthermore, some analyses from academic systems do not reproduce treatment disparities reported in population‐based studies . Further research should clarify to what extent practice‐related factors determine initial management of indolent lymphomas, particularly considering impending changes in the therapeutic landscape.…”
Section: Factors Associated With Administration Of Up‐front Chemothermentioning
confidence: 99%